Analyzing Error pronunciation in Spelling Words by MA Plus Al-Mashduqiah Students Patokan Kraksaan Probolinggo - Ferdiyanto, Feri (Universitas Nurul Jadid, 2019)
This research was desiderated to analyze error pronunciation in spelling words by three classes of MA Plus Al-Mashduqiah students (10th grade-12th grade) Patokan Kraksaan. The error pronunciation occurred as the usual sense in pronouncing the words that not only happen in 10th grade but also in 11th and 12th grade. In order to get data, the participants were given word lists that contained several words and then ordered to pronounce them one by one. These words chose to suspect the common mistakes pronounced by participants. For instance, the word ‘flood’ is pronounced the same as the word ‘door’, the word ‘examine’ is pronounced the same as ‘mine’. Then, an in-depth investigation was used to find out the learners’ consideration pronouncing the words. The result discovered that the learners tended to pronounce the words that referred to other words that contained the same orthography. Using cross-section design, this research randomly selected 60 students. This research found that there were significant gradations among the groups. The amount of error pronunciation was in line with the level of those three groups. The highest error found in 10th grade as new students in that school.